2009
DOI: 10.1007/s11695-009-9864-0
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Perforation During Removal of an Intragastric Balloon

Abstract: The intragastric balloon system is licensed for temporary use in moderately obese patients who have significant health risks related to their obesity and have failed to achieve and maintain significant weight loss with a supervised weight control program alone. Although intragastric balloons are advocated as safe devices, major complications have been described. We report a case of a gastric perforation during the removal of an intragastric balloon. This is the first case reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The balloon was implanted 6 and 9 months, respectively, before symptoms appeared. Gastric perforations with death after insertion of gastric balloon device were reported by Koutelidakis et al [14] and Genco et al [6] and after balloon removal by Ponzo et al [15]. In another case of gastric perforation 2 months following gastric balloon insertion [16], the patient survived after laparotomy and closure of a large linear perforation.…”
Section: Discussionmentioning
confidence: 88%
“…The balloon was implanted 6 and 9 months, respectively, before symptoms appeared. Gastric perforations with death after insertion of gastric balloon device were reported by Koutelidakis et al [14] and Genco et al [6] and after balloon removal by Ponzo et al [15]. In another case of gastric perforation 2 months following gastric balloon insertion [16], the patient survived after laparotomy and closure of a large linear perforation.…”
Section: Discussionmentioning
confidence: 88%
“…There are several contraindications, however, to intragastric balloons, including allergy to the implantable device; anatomic abnormality of the upper gastrointestinal tract; active esophagogastric disease, such as severe esophagitis, hiatal hernia, peptic ulcer disease, Crohn disease, potentially bleeding lesions, and so on; institutions without experience, accreditation, or the ability to resolve complications; and, most importantly and relevant to our case, prior gastric surgery, as it increases the risk of gastric perforation after implantation (grade A recommendation) [1,7]. Also, the use of intragastric balloons entails some limitations, as their durability is limited; hence they are typically removed after 6 months [2]; in addition, there are several known complications, such as prolonged vomiting (mainly during the first week and occasionally for 4 3 weeks), pain, hypokalemia, functional renal insufficiency, gastric ulceration, gastroesophageal reflux disease, spontaneous deflation, intestinal obstruction, gastric perforation, and esophageal perforation, with the last 3 representing major complications [5,8]. Gastric perforation after balloon insertion is a rare, yet life-threatening, complication, with only 6 previous case reports describing 10 cases of this major complication [9].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric perforation after balloon insertion is a rare, yet life-threatening, complication, with only 6 previous case reports describing 10 cases of this major complication [9]. Del Pozo et al reported the first case of gastric perforation after removal of a BIB in a 65-year-old patient; the balloon remained in this patient's stomach for more than the recommended period, and the procedure had been performed by an inexperienced endoscopist [8]. Giardiello et al were, however, the first to report gastric perforation 18 days following insertion of a BIB in a 52-year-old obese woman, who had previously undergone laparoscopic fundoplication for hiatal hernia.…”
Section: Discussionmentioning
confidence: 99%